Optimizing the Implementation of SERVQUAL Principles in Hospital Financial Management to Improve Operational Efficiency and Patient Satisfaction - Bakti, Asri Rani Prasetia; Rahayu, Enik (Mahesa Research Center, 2025)
This article aims to analyze the implementation of SERVQUAL dimensions in financial management at RSU Comal Baru and evaluate its direct influence on service quality and hospital operational performance, especially in terms of financial efficiency. The focus of this study covers five main dimensions of SERVQUAL—Tangibles, Reliability, Responsiveness, Assurance, and Empathy—emphasizing how each dimension affects the effectiveness of the financial system and patient perceptions of hospital financial services. This study uses a qualitative approach with data collection methods through in-depth interviews with financial staff and patients, direct observation of the financial administration process, and analysis of documents related to hospital financial policies and procedures. The data obtained were analyzed using thematic analysis techniques to identify patterns of relationships between SERVQUAL dimensions and increased operational efficiency. The results of the study indicate that the implementation of SERVQUAL dimensions, especially Tangibles, Reliability, Responsiveness, and Empathy, has a direct impact on the operational efficiency of the hospital. Investment in physical facilities, such as a modern administration room, and digitalization of financial processes through more sophisticated software improves the accuracy of recording and the reliability of financial services. Meanwhile, the responsiveness of financial staff in handling patient needs and empathy in providing personal services contribute to increased patient satisfaction. In addition, this study highlights the importance of adjusting service quality improvement strategies to the local context and patient characteristics, considering that Assurance is not a major factor at RSU Comal Baru. This article recommends service quality improvement strategies through staff training to improve technical and communication competencies, updating financial technology to speed up administrative processes, improving coordination between units for operational efficiency, and transparency of financial policies as steps to increase patient trust and the effectiveness of financial services in a sustainable manner.